KINERJA GURU PUSTAKAWAN DALAM PEMBERDAYAAN PERPUSTAKAAN SEKOLAH PADA SMAN 8 BANDA ACEH - Sri Hardianty; Cut Zahri Harun; Niswanto . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2018)
In empowering the school library as a learning resource center requires a good performance from a teacher-librarian. This study aims to determine the palnning and implementation of school library programs, efforts to empower school libraries and factors that support and hinder teacher-librarian in work. This research uses descriptive method with qualitative approach. Data collection techniques are: interview, documentation study and observation. The subjects of the study were: Teacher-Librarian, Principals, Teachers and Students. The results of the research indicate that: (1) The planning of library programs has been discussed together in regular school workshops involving all stakeholders. The library program is centered on three parts: collection development, collection organization and collection service. (2) Of the overall planned program, some have been implemented in accordance with the schedule that has been determined, some are partially wired, and some are not implemented. Teacher-librarian performance assessments fall into the low category. (3) Teachers-librarian doing library empowerment efforts that still revolve around library routine activities. Not yet based on creative and innovative programs. (4) Factors that support the performance of teacher-librarian come from individual teacher-librarian, while those that inhibit performance come from external factors.